The formula for the value of nth term is
= 3n + 1
Step-by-step explanation:
The formula of the nth term in the arithmetic sequence is
, where
- a is the first term of the sequence
- d is the common difference between each two consecutive terms
∵ The first term of an arithmetic sequence is equal to four
∴ a = 4
∵ The common difference is equal to three
∴ d = 3
- Substitute these values in the rule of the nth term
∵ ![a_{n}=a+(n-1)d](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da%2B%28n-1%29d)
∴ ![a_{n}=4+(n-1)3](https://tex.z-dn.net/?f=a_%7Bn%7D%3D4%2B%28n-1%293)
- Simplify it
∴ ![a_{n}=4+3n-3](https://tex.z-dn.net/?f=a_%7Bn%7D%3D4%2B3n-3)
∴ ![a_{n}=1+3n](https://tex.z-dn.net/?f=a_%7Bn%7D%3D1%2B3n)
The formula for the value of nth term is
= 3n + 1
Learn more:
You can learn more about the sequence in brainly.com/question/7221312
#LearnwithBrainly
Answer:
This is true.
Step-by-step explanation:
Step 1: see that √27 is the same as √3*3*3 and thus 3√3
Step 2: remove parenthesis so that 2(1-3√3) becomes 2 - 6√3
Step 3: observe that the equation now becomes 6√3 + 2 - 6√3 = 2
if you simplify any further, you are left with 0=0, which is true.
Comment if there is any step that requires more details...
Answer:
=50×30
= 1500m.
Step-by-step explanation:
field = length = breadth
Answer:
maybe 223 degrees
Step-by-step explanation:
The velocity, slope, of a line is always (y2-y1)/(x2-x1), in this case:
slope=(8-2)/(7-9)=6/-2=-3
m=-3